PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS – ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN - Faisal Akhmad (Universitas Negeri Yogyakarta, 2020)
This research aims to increase student learning outcomes of class XI TKR 3 in the PMKR at SMK N 2 Yogyakarta through the application of the cooperative learning model type Student Teams Achievement Division (STAD). This research is Classroom Action Research (CAR). The research carried out in 2 cycles where each cycle was 1 times meeting. The research subject were student of class XII TKR 3 on the Pemeliharaan Mesin Kendaraan Ringan (PMKR) subjects in thr 2019/2020 academic year with a total of 31 students. Data collection is done by test and observation. Data processing is done quantitatively by seeing the implemetation of the cooperative learning model type Student Teams Achievement Division (STAD) and learning outcomes. The succes criteria determined are minimum 75% of students have reached the Minimum Completion Criteria (MCC) wich is a minimum value of 76,00. The result of this research) is able to increase the learning outcomes of students in class XI TKR 3 in PMKR subjects at SMK N 2 Yogyakarta. Average student learning outcomes increased from data before the action 59,58 to 88,52 in cycle 2. When looking at completeness from the initial data the precentage of students completeness 3,20% increased to 90,30%.